Non-Invasive Monitoring of Cardiac Output in Critical Care Medicine - Nguyen, Lee S.; Squara, Pierre (Frontiers in Medicine, 2017)
Critically ill patients require close hemodynamic monitoring to titrate treatment on a regular basis. It allows administering fluid with parsimony and adjust inotropes and vasoactive drugs when necessary. Although invasive monitoring is considered as the reference method, non-invasive monitoring presents the obvious advantage of being associated with fewer complications, at the expanse of a lesser metrologic performance. A great many methods and devices are now used over the world and this paper focuses on several of them, providing with a brief review of related underlying physical principles and validation papers analysis. Reviewed methods include electrical bioimpedance and bioreactance, respiratory-derived cardiac output monitoring technique, pulse wave transit time, ultrasound cardiac output monitoring, multimodal algorithmic estimation, and inductance thoracocardiography. Quality criteria with which devices were reviewed included: accuracy (closeness of agreement between a measurement value and a true value of the measured), precision (closeness of agreement between replicate measurements on the same or similar objects under specified conditions) and step response change (delay between physiological change and its indication). Our conclusion is that the offer of non-invasive monitoring has improved in the past few years, even though further developments are needed to provide clinicians with tools clearly and completely validated on a metrological basis.